DS-теория. Научные аспекты и перспективы развития - Колесник, В.Г. (Проблеми програмування, 2017)
В работе представлена теория схем декомпозиции как научная теория. Описаны ее атрибуты – парадигма, поле исследований, цель исследований, основная задача, метод решения , основная теоретическая модель – схема декомпозиции. Утилитарная, практическая цель теории – предложить механизм генерации прикладных алгоритмов (не машинного кода). Показано, что схема декомпозиции как описание заменяет описание алгоритма и при этом оста ется декларативным в противоположность описанию алгоритма, как императивному. При этом схема декомпозиции есть описание, исходное для генерации алгоритмов. Описаны виды схем декомпозиции и операции над ними. Описаны алгоритмически релевантные факторы, кото рые следует учитывать при генерации алгоритмов для того, чтобы алгоритмы становились реальными. В работе описана работа по формализации и математическому описанию явлений и объектов теории схем декомпозиции. Предложен механизм контроля выводов и результатов теории. В работе также описано направление развития теории схем декомпозиции. Приоритетное направление соотносится с созданием и развитием системы емких понятий и абстракций. С точки зрения практического применения теории схем декомпозиции, предложен подход подобный тому, что есть в машиностроении – развитие и продвижение передовых технологий по запросу, по потребности – как результат целенаправленных исследований. У роботі представлена теорія схем декомпозиції як наукова теорія. Описано її атрибути – парадигма, поле досліджень, мета досліджень, основне завдання, метод рішення, основна теоретична модель – схема декомпозиції. Утилітарна, практична мета теорії – запропонувати механізм генерації прикладних алгоритмів (не машинного коду). Показано, що схема декомпозиції як опис замінює опис алгоритму і при цьому залишається декларативним на противагу опису алгоритму, як імперативному. При цьому схема декомпозиції є опис, вихідне завдання для генерації алгоритмів. Описано види схем декомпозиції та операції над ними. Описано алгоритмічно релевантні фактори, які слід враховувати при генерації алгоритмів для того, щоб алгоритми ставали реальними. У роботі описана робота з формалізації і математичному опису явищ і об’єктів теорії схем декомпозиції. Запропоновано механізм контролю висновків і результатів теорії. У роботі також описано напрям розвитку теорії схем декомпозиції. Пріоритетний напрямок співвідноситься з створенням і розвитком системи містких понять і абстракцій. З погляду практичного застосування теорії схем декомпозиції запропоновано підхід подібний до того, що є в машинобудуванні, – розвиток і просування передових технологій за запитом, по необхідності – як результат цілеспрямованих досліджень. The work presents the theory of decomposition schemes as a scientific theory. It’s attributes – paradigm, field of research, aim of research, main task, decision method, basic theory model – decomposition scheme were described. Practical aim of the theory is to suggest the mechanism of applied algorithms generation (not machine code). It is shown that the decomposition scheme as a description changes the algorithm description and still remains declarative on the contrary to the algorithm description as imperative. Thereby the decomposition scheme is the description, original for algorithms’ generation. The kinds of decomposition schemes and operations on them have been described. Algorithmically relevant factors which should be considered when generating algorithms in order the algorithms turned real have been described. Working over formalization and mathematical description of the phenomena and objects of the theory of the decomposition schemes have been described here. The mechanism for control of conclusions and results of the theory has been suggested. This work also describes the direction of development of the theory of the decomposition schemes. The priority direction relates to the creation and development of the system of capacious notion and abstractions. From the point of view of the practical application of the theory of the decomposition schemes there the approach which is alike to the one used in machine-building – development and promoting of hi-tech when required – as a result of the targeted research has been suggested.